The Impact of Customer Trust on Customer Loyalty: The Mediating Role of Customer Commitment in Bank Nagari's OLLIN App Users in Padang - Riyadi Nanda; Vidyarini Dwita (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of Customer Trust on Customer Loyalty, specifically examining the mediating role of Customer Commitment among users of the OLLIN Bank Nagari application, Padang Branch. Maintaining customer loyalty is paramount in the competitive banking industry, especially concerning the adoption and continued use of digital platforms like mobile banking applications. The research employed a quantitative approach, utilizing a sample of 200 respondents, which represents the users of OLLIN Bank Nagari in the Padang Branch. Data were collected using questionnaires and analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using the SmartPLS version 4 application. The results indicate that Customer Trust significantly and positively influences Customer Loyalty. Furthermore, Customer Trust also has a positive and significant effect on Customer Commitment. Crucially, the direct relationship between Customer Commitment and Customer Loyalty is found to be positive and significant. The mediation analysis confirms the hypothesis, showing that Customer Commitment successfully mediates the influence of Customer Trust on Customer Loyalty among OLLIN Bank Nagari users. These findings underscore the importance of building robust customer trust as a foundation that, when fostered into a sense of commitment, effectively enhances and sustains customer loyalty towards the mobile banking application.